Task-control adaptation in task switching: Uncovering the mechanisms behind the list-wide proportion valency effect. - Moretti, Luca; Koch, Iring (Memory & Cognition, 2026)
The term conflict adaptation refers to the up- or down-regulation of control processes depending on the likelihood and recency of conflict occurrence. While most research on conflict adaptation has examined single-task settings (e.g., the Stroop paradigm), in a recent study we investigated whether similar phenomena are also present in task switching. In that study, we asked whether control over stimulus-induced task conflict is modulated depending on its frequency. We operationalized stimulus-induced task conflict with the valency effect, namely the performance difference between bivalent-congruent trials (i.e., stimuli affording two tasks but only one correct response) and univalent trials (i.e., stimuli affording one task). Manipulating the proportion of bivalent trials across blocks, we found that the valency effect was reduced in majority-bivalent blocks, suggesting that task-conflict control is upregulated under high-conflict conditions. Building on these findings, the present study presents three experiments designed to uncover the mechanisms behind task-conflict control adaptation in task switching. In particular, we aimed to assess whether task-conflict control is adapted in a transient or in a sustained fashion. In Experiment 1, we ruled out the possibility that control adaptation arises from transient increases in attentional biasing following cue onset. In Experiments 2a and 2b we found evidence that the mechanisms responsible for upregulating task-conflict control act in a task-specific fashion, suggesting that, contrary to single-task paradigms, control adaptation occurs transiently rather than sustainedly. We conclude that in task-switching contexts, conflict adaptation is achieved by modulating reactive control mechanisms triggered after stimulus onset.